Ground Control Procedures in Western Australian Underground Mines - a Critical Review (The Australasian Institute of Mining and Metallurgy, 1992)
A review of ground control procedures in Western Australian underground mines is presented. Geotechnical input into initial mine design and methods of ground control is rare. As a result, the frequency of unexpected rockfalls is comparatively high, with over three quarters of the mines adopting non-specialist ground control designs experiencing unexpected falls-of-ground. In contrast, mines that provide some level of specialist input into initial ground control design experience decreased rockfall frequencies.